Associations of fibroblast growth factor 23, vitamin D and parathyroid hormone with 5-year outcomes in a prospective primary care cohort of people with chronic kidney disease stage 3 - Shardlow, Adam; McIntyre, Natasha J.; Fluck, Richard J.; McIntyre, Christopher W.; Taal, Maarten W. (BMJ Publishing Group, 2017)
Objectives Vitamin D deficiency, elevated fibroblast growth factor 23 (FGF23) and elevated parathyroid hormone (PTH) have each been associated with increased mortality in people with chronic kidney disease (CKD). Previous studies have focused on the effects of FGF23 in relatively advanced CKD. This study aims to assess whether FGF23 is similarly a risk factor in people with early CKD, and how this risk compares to that associated with vitamin D deficiency or elevated PTH.